VARIAÇÃO ESPACIAL DAS CONCENTRAÇÕES DE CÁDMIO E MANGANÊS EM SOLO OCUPADO POR ATERRO SANITÁRIO - Kemerich, Pedro Daniel da Cunha; Flores, Carlos Eduardo Balestrin; Borba, Willian Fernando de; Flores, Bruno Acosta; Descovi Filho, Leônidas Luiz Vocatto; Barros, Guilherme; Gerhardt, Ademir Eloi; Rodrigues, Alexandre Couto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
Landfills are configured as a correct and safe way of disposal of solid waste, but require serious study for your choice. Therefore this study aimed to determine the potential for contamination of soil by cadmium and manganese as a result of the occupation by landfill. In the present study, there was a borehole to collect the samples being made according to the existing topography at the site and preferential flow of surface water, considering 10 collection points called P1 to P10. Analyses were performed by Shimadzu Energy Dispersion X-ray Fluorescence Spectrometer Rany, Serie EDX-720. Manganese showed high levels at all points studied with P4 at the highest concentration to 200 cm (11576.46 mg kg-1) has the lowest concentration shown in P7 was 300 cm (516 237 mg kg-1) due high concentration of this element, it becomes harmful to the soil and vegetation at the site. As for Cadmium higher concentrations occurred at P7 at 100 cm depth (57238 mg kg-1) and P9 at 300 cm depth (36319 mg kg-1). Based on this, it was concluded that the highest concentrations of cadmium occurred at depths ranging from 100 to 200 cm, showing that there was an increased concentration with depth. Already vulnerability has been classified as low, thus presenting little susceptible to contamination of groundwater.